KOMUNIKASI KEBIJAKAN KELUARGA BERENCANA PRIA DI KECAMATAN TUGU KOTA SEMARANG - Maulida Syifaurrochmah; Kismartini Kismartini; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2023)
The percentage of men's family planning (KB) policy achievements in Tugu District shows that the number of men with family planning is only 3.71%, consisting of 0.24% (MOP) and 3.47% (Condoms), as well as the lack of promotion through various communication media resulting in There is a myth about male birth control that is developing in society. This research analyzes the communication of men's family planning policies in Tugu District, Semarang City and analyzes the inhibiting factors in this policy communication. A policy implementation model approach that focuses on policy communication to analyze aspects of transmission, clarity and consistency. Research looking at communication transmission shows that it is not optimal, because coordination is rarely carried out, there is a lack of promotional media for men's family planning, and there is no distribution of duties and functions of the Priyo Utomo Association as a men's family planning group. Then, clarity of communication is still lacking, because there is no special content that explains male family planning comprehensively to the target group. In addition, communication is not carried out consistently to policy implementers. Factors inhibiting policy communication include the level of knowledge/education of family planning officers; limited manpower/human resources for family planning officers; as well as a limited budget for socialization and promotion of male family planning activities as well as activating the Priyo Utomo association. It is necessary to develop a broader communication strategy to reach information, involve the role of stakeholders and communication media, make special discussions on male family planning, and optimize the priyo utomo community